Anodic alumina photonic crystals: Structure engineering, optical properties and prospective applications. (March 2023) - Shang, Guoliang; Bi, Dongxue; Gorelik, Vladimir Semenovich; Fei, Guangtao; Zhang, Lide
Abstract: Anodic alumina photonic crystal is a porous periodic dielectric structure and has been extensively studied by researchers due to its straightforward preparation processes, porous features, high chemical, and thermal stability. The photonic structure consists of periodic layers of dielectrics with strong light scattering from the porous feature that allows for versatile tailoring of the optical properties of the anodic alumina photonic crystal. In this review, the related theories, application-oriented structure tailoring, optical properties, and selected applications are summarized. Finally, we forecast future research and applications. Graphical Abstract: ga1